Localising Victory : GE 14 and the electoral contests in Johor and Kelantan - Mohamed Nawab Osman,; Rashaad Ali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The 14th Malaysian Election heralded a new dawn for Malaysian politics and society. The change of government was not predicted by observers of Malaysian politics and came as a surprise for many. Two states in particular stood out in the election as a misnomer, the states of Kelantan and Johor. The cases of Kelantan and Johor are interesting for a number of reasons. First, these states are considered stronghold states of the two Malay based political parties, the United Malays National Organization (UMNO) and the Pan-Malaysian Islamic Party (PAS). Second, the results in both states were largely unexpected with most observers predicting that UMNO will retain Johor and that PAS will lose Kelantan. Lastly, both states can be described as ‘maverick’ states. Under Malaysia’s current federal system, these states have historically manifested a strong independent streak. In the case of Johor, the bangsa Johor, a kind of state level nationalism that is centred around a Johorean identity can be observed whereas in the case of Kelantan, the conception of Kelantan as an abode of Islam has shaped the Kelantanese identity. This paper examines how both states that demonstrated similar localized election strategies yielded divergent results, with Kelantan continuing to support PAS while Johor abandoned UMNO-BN.